Femoral intraosseous rhabdomyosarcoma: a case report and literature review - Dan Carai Maia Viola; Nathalia Sundin Palmeira de Oliveira; Jairo Greco Garcia; Marcelo de Toledo Petrilli; Carla Renata Pacheco Donato Macedo; Maria Teresa Seixas Alves; Reynaldo JesusGarcia (Brazilian Journal of Oncology)
Introduction: Rhabdomyosarcoma is the most common soft tissue sarcoma in childhood. However, primary bone rhabdomyosarcoma is a rare entity with some few cases reported. Case Report: We present a case of a 19-year-old female patient referred from another service with three months history of a bone tumor on the femur. The first anatomopathological study was consistent with high-grade osteogenic sarcoma. After revision exams and analysis of surgically resected tumor, the primary osseous rhabdomyosarcoma was confirmed. The patient had undergone tumor resection and reconstruction with mega prosthesis. After surgery, she received chemotherapy following rhabdomyosarcoma protocol. Conclusion: Primary osseous rhabdomyosarcoma is a rare but important differential diagnosis to be thought on atypical presentation of primary bone sarcomas.